Arsenite-induced apoptosis can be attenuated via depletion of mTOR activity to restore autophagy. Issue 1 (20th November 2018) - Wu, Chien-Wei; Lin, Pei-Jung; Tsai, Jia-Shiuan; Lin, Chih-Ying; Lin, Lih-Yuan
Graphical Abstract: Abstract: Arsenic and its compounds are toxic environmental pollutants and known carcinogens. We investigated here the mechanism of arsenite-induced damage in renal cells. Treating human embryonic kidney cells (HEK293) with sodium arsenite reduces cell viability in a dose- and time-dependent manner. The decline of cell viability is due to apoptotic death since arsenite treatment reduces Akt activity and the Bcl2 level but increases caspase 3 activity and the cytochrome c level. These effects can be reverted by the addition of an apoptosis inhibitor. PTEN, the upstream negative regulator of Akt activity, was also reduced with arsenite treatment. Noticeably, PTEN markedly increased in the insoluble fraction of the cells, suggesting a cell failure in removing the damaged proteins. Arsenite treatment activates a variety of signaling factors. Among them, ERK and JNK are associated with autophagy via regulating the levels of LC3 and p62. With arsenite administration, the LC3 and p62 levels increased. However, lysosomal activity was decreased and led to the decline of autophagic activity. The addition of rapamycin, the mTOR inhibitor, activated the autophagic pathway that accelerated the removal of damaged proteins. The recovery of autophagy increased the viability of arsenite-treated cells. Similar to rapamycin treatment, the knockdown of mTOR expression also enhanced the viability of arsenite-treated cells. Both rapamycin treatment and mTOR knockdown enhanced ERK activity further, but reduced JNK activity and the p62 level in arsenite-treated cells. Lysosomal activity increased with the depletion of mTOR, indicating an increase of autophagic activity. These results reveal the critical role of mTOR in regulating the cell fate of arsenite-exposed renal cells.